Diagnostic and Clinical Patterns of Newly Diagnosed ANCA-Associated Vasculitis Before and After the 6 February 2023 Kahramanmaraş Earthquakes: A Multicenter Retrospective Study from Affected Provinces - Sezgin Zontul; Gezmiş Kimyon; Fuat Albayram; Anıl Göçer; Rabia Sağır; Aylin Dolu Karaca; Elif İnanç; Zeynep Kaya; Mesude Seda Aydoğdu; İpek Balıkçı Çiçek; Gözde Yıldırım Çetin; Servet Yolbaş (Journal of Clinical Medicine, 2026)
Background/Objectives: The relationship between large-scale natural disasters and antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) remains uncertain. This study compared crude case numbers, diagnostic patterns, and clinical characteristics of newly diagnosed AAV before and after the 6 February 2023 Kahramanmaraş earthquakes in Türkiye. Methods: This multicenter retrospective study included patients newly diagnosed with AAV between 6 February 2020 and 5 February 2026 at five tertiary referral centers in four provinces heavily affected by the earthquakes. Equal 36-month pre- and post-earthquake periods were compared. Demographics, AAV subtype, ANCA serology, biopsy-confirmed diagnosis, organ involvement, Birmingham Vasculitis Activity Score (BVAS), laboratory findings, treatments, and recorded outcomes were evaluated. Results: A total of 127 patients were included: 58 (45.7%) before and 69 (54.3%) after the earthquakes. The crude number of cases was numerically higher after the earthquakes, but the difference was not statistically significant (p = 0.375). AAV subtype, ANCA serology, organ involvement, BVAS, inflammatory markers, renal function, and most laboratory findings were comparable. Biopsy-confirmed diagnoses were significantly less frequent in the post-earthquake period than in the pre-earthquake period (46.4% vs. 70.7%, p = 0.010). Treatment patterns were comparable between the two periods. Although the crude proportions of recorded outcomes did not differ significantly, these comparisons were limited by the substantially shorter follow-up duration in the post-earthquake group and should not be interpreted as evidence of comparable prognosis. Conclusions: In major tertiary referral centers serving earthquake-affected provinces, crude AAV case numbers and baseline clinical phenotypes were largely comparable before and after the earthquakes. These crude case numbers should not be interpreted as incidence estimates, because reliable population denominators were unavailable after the earthquakes. The significant reduction in biopsy-confirmed diagnoses may reflect post-disaster changes in diagnostic healthcare pathways. These real-world data provide an important regional overview of newly diagnosed AAV after a major natural disaster.